A comparative pharmacokinetic study of three flavonoids and three anthraquinones in normal and gastrointestinal motility disorders rat plasma after the oral administration of Wei‐Chang‐Shu tablet using high‐performance liquid chromatography–tandem mass spectrometry. (5th June 2017) - Ren, Yan; Zhao, Weiwei; Zhao, Juanjuan; Chen, Xiangming; Yu, Chen; Liu, Mengan
Abstract: A simple, fast and reliable high‐performance liquid chromatography–tandem mass spectrometry method was developed and validated for the simultaneous quantification and pharmacokinetic study of three flavonoids (liquiritigenin, isoliquiritigenin and formononetin) and three anthraquinones (emodin, rhein and aloe‐emodin), which are the bioactive ingredients of Wei‐Chang‐Shu tablet found in rat plasma. After extraction by liquid–liquid extraction with ethyl acetate, chromatographic separation was achieved on an Agilent Zorbax SB‐C18 column (4.6 × 150 mm, 5 μm) at a flow rate of 1 mL/min by gradient elution using 0.1% aqueous acetic acid and acetonitrile. The detection was performed using a triple quadrupole mass spectrometer equipped with electrospray ionization source in the negative ionization and selected reaction monitoring mode. Method validation was performed in terms of specificity, carryover, linearity ( r  > 0.99), intra−/inter‐day precision (1.0–10.1%), accuracy (relative error, <7.6%), stability (0.6–13.2%), extract recovery (74.9–91.9%) and matrix effect (89.1–109%). The lower limits of quantification of the six analytes varied from 0.92 to 10.4 ng/mL. The validated method was successfully applied to compare the pharmacokinetic properties of Wei‐Chang‐Shu tablet in normal rats and in rats with gastrointestinal motility disorders. The results indicated that there were obvious differences in the pharmacokinetic behavior between normal and model rats. This study will be helpful in the clinical application of Wei‐Chang‐Shu tablet.